ELECTRODEPOSITION AND PROPERTIES OF IRON DEPOSITS OBTAINED IN A MAGNETIC FIELD OF WEAK INDUCTION - MISHCHENKO, Vladyslava; KOVALYOV, Stanislav (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper presented the electrodeposition, morphology and properties of iron deposits were obtained using a low-induction magnetic field of 0.001 T in the electrocrystallization process. The vector of magnetic field induction was directed perpendicular to the electrode surface. Iron deposits were obtained in an electrolyte FeSO4·7H2O – 1.5 mol/l and Al2(SO4)3·18H2O – 0.15 mol/l. The current density was 7 A/dm2. Deposits were obtained on a copper base. The influence of the magnetic field on the process of electrodeposition of deposits was studied using the method of stationary potentiometry and cyclic voltammetry. Determination of the influence of the magnetic field on the morphology of deposits was carried out using scanning electron microscopy. Determination of the properties of the obtained iron deposits was carried out by measuring microhardness, reflectivity and corrosion resistance. Studies have shown that a magnetic field with an inductance of 0.001 T affects the processes of electrodeposition of an iron deposit, increasing its overvoltage by more than 1 volt. The morphology of the deposits does not change significantly, but the crystallites obtained in the magnetic field have a more rounded shape and the surface of the deposit is more uniform. The microhardness of deposits obtained by electrodeposition without the use of a magnetic field was 2610 MPa, and with a magnetic field - 2720 MPa. The reflectivity of deposits obtained in a magnetic field is 17% higher. The corrosion resistance of deposits obtained in a magnetic field is approximately two times higher. After conducting corrosion studies, the microhardness of the deposits obtained using a magnetic field did not change (2630 MPa), however, the microhardness of the deposits obtained under normal conditions decreased by approximately two times. Electrolysis parameters for maximum corrosion resistance, microhardness and reflectivity are proposed in the work.
Keywords: electrodeposition; magnetic field; iron deposits; corrosion resistance; microhardness